Lipid-Lowering Efficacy of the Capsaicin in Patients With Metabolic Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jiang, Zhonghui; Qu, Hua; Lin, Gongyu; Shi, Dazhuo; Chen, Keji; Gao, Zhuye (Frontiers in Nutrition, 2022)
Background Patients with metabolic syndrome (MetS) have increased cardiovascular risk. Capsaicin (CAP) has been shown to reduce lipids, but efficacy for patients with MetS is unknown. Methods A systematic review was performed according to PRISMA guidelines, to compare the effects of CAP against a placebo. Differences in the weight mean difference (WMD) with 95% confidence intervals (95% CI) were then pooled using a random effects model. Results Nine randomized controlled trials including 461 patients were identified in the overall analysis. CAP significantly decreased total cholesterol (TC) (WMD = −0.48, 95% CI: −0.63 to −0.34, I2= 0.00%) and low-density lipoprotein cholesterol (LDL-C) (WMD = −0.23, 95% CI: −0.45 to −0.02, I2 = 68.27%) among patients with MetS. No significant effects of CAP were found on triglycerides (TG) or high-density lipoprotein cholesterol (HDL-C) (WMD = −0.40, 95% CI: −1.50 to 0.71, I2 = 98.32%; WMD = −0.08, 95% CI: −0.21 to 0.04, I2 = 86.06%). Subgroup analyses indicated that sex and intervention period were sources of heterogeneity. The results revealed that CAP decreased TG levels in women (WMD = −0.59, 95% CI: −1.07 to −0.10) and intervention period <12 weeks (WMD = −0.65; 95% CI: −1.10 to −0.20). And there was no potential publication bias according to funnel plot, Begg' test and Egger regression test. Conclusions CAP supplementation is a promising approach to decreasing TC and LCL-C levels in patients with MetS. However, short-term (<12 weeks) use of CAP in women may also reduce TG levels. Systematic Review Registration Identifier: CRD42021228032.